The Relationship of Teacher Perceptions of Educational Standards and Madrasah Head Leadership Style in Improving Teacher Performance - Ahmad Muhid; Dalman Dalman; Adam Hafidz Al Fajar; Yuni Lasma; Bima Fandi Asy'arie (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research aims to discover: (1) The influence of teacher perceptions about educational standards on teacher performance. (2) The principal's leadership style influences teacher performance. (3) The influence of teachers and the principal's leadership style on teacher performance. This research focuses on Madrasah Ibtidaiyah Negeri (MIN) in West Tulang Bawang Regency, Lampung. This research method includes correlational/associative with a quantitative approach. Data collection techniques are carried out through observation, questionnaires and documentation. First, the regression analysis calculated t value reached 2.594, exceeding the t table value of 0.320 with a significance of 0.014, lower than 0.05. In addition, the teacher's perception of educational standards (R Square) is 0.157, showing that the principal's leadership can explainaround 15.7% of teacher performance. Second, the regression analysis calculated t value for teacher perceptions reached 3.583, exceeding the t table value of 0.320, with a significance value of 0.001 which is less than 0.05. Third, the magnitude of the influence of teacher perceptions on educational standards is (R Square) 0.263, which indicates that around 26.3% of teacher performance can be explained by teacher professionalism. Third, with the calculated F regression results of 9.437, greater than the value of 3.27, with a significance value of 0.001, less than 0.05. In addition, the influence of teachers' perceptions of educational standards and principals' leadership styles (R Square) of 0.350 indicates around 35% of variation in teacher performance.